Comprehensive evaluation and hierarchical management method of operator’s communication room based on users and business - Chenggui ZHOU (Dianxin kexue)
The growing network scale of operators makes the network maintenance strength and cost more limited.How to use the limited cost to carry out high-quality network operation and maintenance has become a new challenge.As the important core resource of operator network,the fine management of communication roomsare is very necessary.A user-oriented and business-oriented hierarchical operation and maintenance management idea for operators’ communication room was presented.The multi-factor weighting method was used to evaluate the communication rooms comprehensively by the user and business data carried by the communication rooms.The communication rooms were classified according to the user and business distribution.